Postures épistémiques d’enseignants-tuteurs en contexte d’apprentissage par problèmes (APP) : les cas de la médecine et du génie - Christelle Lison; Denis Bédard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Major pedagogical innovations implemented by some programs lead teachers to a change of role (Bédard & Béchard, 2009). We hypothesized that their ability to align their interventions with pedagogical precepts of innovation is largely dependent on their intellectual posture within the meaning of Perry (1970, 1981). To check the value of this hypothesis, we met 13 teacher-tutors evolving in two 1rst cycle programs which have adopted problem-based learning (PBL) : a medicine program and an engineering program. Following the analysis of data collected by semi-structured interviews, observations and self-confrontation interviews, we note first of all that medicine and engineering teacher-tutors do not take the same epistemic posture, anyway during classroom observations. These results are explained partly by how the PBL has been implemented in each program. Other elements such as the group of student and the problem situation also help to explain this gap, although in a minor way. Finally, we note that the teacher-tutors’ speech (semi-structured interviews), the majority of the time, consistent with their actions (observations) and that they are generally aware of the posture they adopt (self-confrontation interviews). This is also consistent with the style of animation (Vierset, Bédard & Foidart, 2009) they put in place during the two PBL meetings.